Correlation between podoplanin expression and extracapsular spread in squamous cell carcinoma of the oral cavity using subjective immunoreactivity scores and semiquantitative image analysis. Issue 1 (20th July 2016) - Mermod, Maxime; Bongiovanni, Massimo; Petrova, Tatiana V.; Dubikovskaya, Elena A.; Simon, Christian; Tolstonog, Genrich; Monnier, Yan
Abstract: Background: The correlation between podoplanin expression and extracapsular spread in head and neck squamous cell carcinoma (HNSCC) has never been reported. The purpose of this study was to assess the predictive value of podoplanin expression for this parameter. Methods: Subjective immunoreactivity scores and semiquantitative image analysis of podoplanin expression were performed in 67 patients with primary oral squamous cell carcinoma and in their corresponding lymph nodes. Neck classification showed 34 cases (51%) of pN0 and 33 cases (49%) of pN+. Correlation between the levels of podoplanin expression and the histopathological data was established. Results: In lymph nodes, a high level of podoplanin expression correlated with the presence of extracapsular spread by multivariate analysis ( p = .03). A strong correlation between subjective and semiquantitative image analysis was observed ( r = 0.77; p < .001). Conclusion: A high level of podoplanin expression in lymph node metastases of oral squamous cell carcinoma is independently associated with extracapsular spread. © 2016 Wiley Periodicals, Head Neck 39: 98–108, 2017